Sex-Specific Environmental Impacts on Initiation and Progression of Multiple Sclerosis - Leffler, Jonatan; Trend, Stephanie; Gorman, Shelley; Hart, Prue H. (Frontiers in Neurology, 2022)
The immunological mechanisms that contribute to multiple sclerosis (MS) differ between male and females. Females are 2-3 times more likely to develop MS compared to males, however the reason for this discrepancy is unknown. Once MS is established, there is a more inflammatory yet milder form of disease in females whereas males generally suffer from more severe disease and faster progression, neural degradation, and disability. Some of these differences relate to genetics, including genetic control of immune regulatory genes on the X-chromosome, as well as immune modulatory properties of sex hormones. Differences in MS development may also relate to how sex interacts with environmental risk factors. There are several environmental risk factors for MS including late-onset Epstein Barr virus infection, low vitamin D, low UV radiation exposure, smoking, obesity, and lack of physical activity. Most of these impact males and females differently, either due to biological or immunological processes or through behavioural differences. In this review, we explore these differences further and focus on how the interaction of environmental risk factors with sex hormones may contribute to significantly different prevalence and pathology of MS in males and females.